Analysis and optimization of transient heat dissipation characteristics of high power resistors with a sensible heat storage method. (25th May 2023) - Yu, Siyong; Han, Dong; He, Weifeng; Zhou, Maolin; Zhu, Lei; Gao, Yanfei; Cui, GaoYU; Peng, Tao
Highlights: The heat dissipation of transient high voltage electronic equipment is analyzed. The more reliable natural heat dissipation method is adopted. Enhance heat dissipation by strengthening the heat conduction and sensible heat storage. Iron rod and ceramic are used to enhance heat conduction and heat storage. Abstract: The load voltage of the resistor will rise sharply when there is a control imbalance or short circuit in the circuit, and the resistance wire will fuse in a matter of seconds, causing the resistor to burn. Designing resistors with superior transient heat dissipation capabilities is therefore crucial. In this work, using sensible heat storage, various sizes of iron rods are developed and inserted into the ceramic to enhance heat transfer by utilizing iron's high thermal conductivity. In addition, to maximize the material's high thermal capacity for heat storage, ceramic blocks in the form of dumbbells were also put between the ceramic rods inside the resistor. The results demonstrated that both designs could enhance the resistor's capability to dissipate heat. When iron rods with a diameter of 7 mm are inserted, the device's capacity for heat storage is raised by 19.09 %, and its heat storage efficiency increases by 16.24 %. The device's capacity for heat storage can be raised by 20.5 %, and its heat storage efficiency can be raised by 18.23 % by embedding a ceramic dumbbell with a 9 mm diameter.